Catalytic CO2 conversion to C1 value-added products: Review on latest catalytic and process developments - Noor Yusuf (15748120) (2023)
With the increase in CO2 emissions in the last decades, CO2 capture and storage and CO2 capture and utilization technologies have been interesting topics in literature and industry. CO2 direct utilization for oil gas recovery is a mature utilization route in the oil and gas industry. CO2 is the focus of many technological and academic studies for its potential as a source of carbon for producing value-added chemical products and synthetic fuels. CO2 utilization technologies are grouped based on the production route, such as electrochemical, catalytic, photocatalytic, photosynthetic, biological, and depolymerization. This review discusses the latest technological innovations in catalyst developments for direct CO2 utilization to C1 value-added products and fuels. Amongst the various potential products, CO2 conversion to dimethyl carbonates, methanol, formic acid, syngas, and methane using different homogenous and heterogeneous catalytic systems was discussed. The most recent advancements for process exploitations were highlighted for each utilization route to evaluate the maturity of the proposed systems technically and economically. The review revealed that thermally-driven CO2 catalytic conversion to methanol, synthesis gas and methane are the most promising for industrial deployment. Furthermore, Green hydrogen and the cost of energy production are the key obstacles to large-scale deployments of CO2 utilization. However, supported by the latest advancements in renewable energy production, the discussed utilization routes would be more applicable in the near future. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2023.128178